Code-Switching, Translanguaging, and Linguistic Identity in Multilingual Arabic Language Learning - Sahrani; Azis, Abdul; Lu’luil Maknun; Muhammad Mugni Assapari (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
Abstract This qualitative case study examines how code-switching and translanguaging operate in multilingual Arabic language classrooms and how they shape learners’ linguistic identity. Grounded in sociolinguistic variation theory and translanguaging perspectives, the study was conducted in an Arabic Language Education programme at an Indonesian university. Participants were 25 undergraduate students and 2 instructors. Data were collected through six classroom observations, semi-structured interviews with ten students and two instructors, and analysis of instructional documents. The findings show that learners shifted among Arabic, Bahasa Indonesia, English, and local languages when they faced lexical, grammatical, or conceptual difficulty. Instructors also used strategic code-switching to clarify Arabic concepts and sustain participation. These practices supported comprehension, reduced anxiety, and enabled students to negotiate academic, religious, and social identities. Arabic was associated with pride, religious affiliation, and academic belonging, whereas rigid Arabic-only expectations sometimes limited participation. The study argues that selective code-switching and translanguaging can function as pedagogical resources when they support, rather than replace, Arabic proficiency development. Abstrak Penelitian studi kasus kualitatif ini mengkaji bagaimana alih kode dan translanguaging berlangsung dalam kelas bahasa Arab multibahasa serta bagaimana keduanya membentuk identitas linguistik mahasiswa. Berlandaskan teori variasi sosiolinguistik dan perspektif translanguaging, penelitian dilakukan pada program Pendidikan Bahasa Arab di sebuah universitas di Indonesia. Partisipan terdiri atas 25 mahasiswa sarjana dan 2 dosen. Data dikumpulkan melalui enam observasi kelas, wawancara semi-terstruktur dengan sepuluh mahasiswa dan dua dosen, serta analisis dokumen pembelajaran. Temuan menunjukkan bahwa mahasiswa berpindah antara bahasa Arab, Bahasa Indonesia, bahasa Inggris, dan bahasa daerah ketika menghadapi kesulitan leksikal, gramatikal, atau konseptual. Dosen juga menggunakan alih kode secara strategis untuk menjelaskan konsep bahasa Arab dan menjaga partisipasi kelas. Praktik ini membantu pemahaman, mengurangi kecemasan, dan memungkinkan mahasiswa menegosiasikan identitas akademik, religius, dan sosial. Bahasa Arab dikaitkan dengan kebanggaan, afiliasi religius, dan keberadaan akademik, sedangkan tuntutan penggunaan bahasa Arab secara kaku kadang membatasi partisipasi. Penelitian ini menegaskan bahwa alih kode dan translanguaging yang selektif dapat menjadi sumber pedagogis apabila mendukung, bukan menggantikan, pengembangan kemahiran bahasa Arab.